2020
DOI: 10.1002/anie.201913373
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent‐Iodine‐Mediated Carbon–Carbon Bond Cleavage and Dearomatization of 9H‐Fluoren‐9‐ols

Abstract: A transition‐metal‐free synthesis of spiro compounds from 9H‐fluoren‐9‐ols mediated by hypervalent iodine is reported. In this reaction, an unprecedented β‐carbon elimination of tertiary alkoxyliodine(III) to form new diaryliodonium salts is proposed. The obtained phenol intermediates undergo oxidative dearomatization to furnish a class of oxo‐spiro compounds. This domino reaction significantly increases the complexity of these molecules and shows excellent regio‐ and stereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…Satisfyingly,t he reaction of 11-methyl-7-phenyl-7H-benzo[c]fluoren-7-ol 1u or its chlorinated analogue 1v selectively yielded 2u and 2v each as as ingle isomer, which was unambiguously confirmed by single-crystal X-ray diffraction analysis of 2u. [17] It indicated that the reaction favored cleaving the naphthylÀC(sp 3 )b ond. Surprisingly,t he reaction of 1w,b earing am ethyl group adjacent to the cyclopentanol ring, selectively cleaved the more steric C-(aryl) À C(sp 3 )bond to provide 2w in high yield.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Satisfyingly,t he reaction of 11-methyl-7-phenyl-7H-benzo[c]fluoren-7-ol 1u or its chlorinated analogue 1v selectively yielded 2u and 2v each as as ingle isomer, which was unambiguously confirmed by single-crystal X-ray diffraction analysis of 2u. [17] It indicated that the reaction favored cleaving the naphthylÀC(sp 3 )b ond. Surprisingly,t he reaction of 1w,b earing am ethyl group adjacent to the cyclopentanol ring, selectively cleaved the more steric C-(aryl) À C(sp 3 )bond to provide 2w in high yield.…”
Section: Methodsmentioning
confidence: 99%
“…T he structure of 4b was further confirmed by single-crystal X-ray analysis. [18] In aqueous acidic medium, 1a underwent nucleophilic ring opening to produce ab iphenyl product 5 in excellent yield [Scheme 2,Eq. (4)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of the propensity of 2-([1,1′-biphenyl]-2yl)propan-2-ol (117) to undergo multiple C−C bond and directed C−H bond cleavages, triphenylenes 119 could be efficiently synthesized by reaction of 117 with 1,2-dibromoarenes (118) (Scheme 20).…”
Section: β-Aryl Elimination With Palladiummentioning
confidence: 99%
“…47 The radical anion (FL .-) and dianion (FL -2 ) arising from 9-fluorenone exhibits good stability and versatile reactivity. Moreover, fluorene and 9H-fluoren-9-ol as privileged scaffolds have been extensively explored in the synthesis of organic light emitting materials 48 , biaryl Page 3 of 25 CCS Chemistry atropisomers [49][50] and spiro molecules 51 . In this context, 9-fluorenone is selected as a coupling partner to investigate the electrochemical cross-coupling reaction of alcohols, and access synthetically useful products (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%